Tourist satisfaction toward intracity coaches’ services in Melaka city: a case study of Panorama Double Decker / Muhammad Musa and Nuraini Abdul Samad - Musa, Muhammad; Abdul Samad, Nuraini (2014)
This study investigates the use of public transport (intracity coach’s services) by tourists in the city of Melaka. It seeks to understand how passengers perceive public transport services and which factors influence their level of satisfaction. A questionnaire is using in collecting survey which are 70 visitors by implementing nominal and ordinal scale in Statistical Package for Social Sciences (SPSS). Other than that, in evaluating the extent of tourist satisfaction to a statement indicating a degree of agreement or disagreement is using a Likert Scale. In obtaining the result, the relationship between services towards tourist’s satisfaction will evaluate and their theoretical relationship will make both scientific and practical contribution in future research. In this study there are two factors that influence the tourist’s satisfaction, there are soft quality and functionality quality. Soft quality is divided into bus cleanliness, seat availability, bus’s driver behavior, safety, information and bus stop condition. While for functionality quality, it divides into frequency, price and time. From the aspects of quality management, soft quality recorded a better result of mean than functionality quality. Soft quality’s mean result is 3.63, while for functionality quality’s mean result only recorded 3.31, lower than soft quality. Other than that, the result also showed that overall tourist satisfaction is satisfied with the safety and service provided, they recorded same mean’s result 3.86. The result has showed that most of tourists are satisfied with those aspects. The result from the study shows that soft quality gives an impact to the tourist satisfaction rather than functionality quality.